Average and Maximum Papilla Heights around Dental Implants in the Anterior Maxillary Region: A Retrospective Clinical Study - Gholam Ali Gholami; Soheil Hariri; Reza Amid; Leyla Roghanizadeh; Mahdi Kadkhodazadeh; Amirreza Mehdizadeh; Navid Youssefi (International Journal of Dentistry)
Objective. The aim of this study was to determine the average and maximum height of the papilla around maxillary anterior implants in respect of neighboring structures and location of implants. Materials and Methods. 92 dental implants from 63 patients were investigated in this study. Those implants were placed in the anterior maxillary region and had been loaded for a minimum of one year. After receiving written consent, clinical data including the height of interproximal papillae adjacent to the tooth/implant/pontic were obtained through clinical observation. The independent t-test or ANOVA, the regression modeling, and generalized estimating equation (GEE) models were used for statistical analysis (p<0.05). Results. Papilla height was calculated as 2.8 mm (1–5.5 mm) for implant-tooth sites, 2.6 mm (1–4 mm) in implants beside pontics, and 2.5 mm (1–3.5 mm) for implants adjacent to implants. Despite the lack of a significant difference in the mean papilla height in the studied groups, the maximum values of papilla heights were significantly different. Conclusions. In this study, no significant differences were found in papilla height mean values in relation to neighboring structures or location of implants in the anterior maxilla. However, the maximum values of papilla heights were observed around implants next to natural teeth.